Economic Development, Democratisation and the Rule of Law in Ghana and Nigeria - Olayinka, Olaniyi Felix (Palgrave Macmillan Springer Nature, Switzerland, 2022)
Democracy is a system of government in which the people rule themselves either directly or through chosen representatives.1 It is often called a game of numbers, since the majority rule in a constituency while the minority make their presence felt, all the same. The electorates choose leaders at periodic elections to represent them, and these elections assume that representatives and electorates have settled on the manner of human and national development that the elected representatives should effect. Active participation of the electorates is thus seen in terms of emergence